2012
DOI: 10.2967/jnumed.111.094029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of 18F-AZD4694, an Amyloid-β–Specific PET Radioligand

Abstract: Pioneered with the invention of 11 C-Pittsburgh compound B, amyloid-b imaging using PET has facilitated research in Alzheimer disease (AD). This imaging approach has promise for diagnostic purposes and evaluation of disease-modifying therapies. Broad clinical use requires an 18 F-labeled amyloid-b radioligand with high specific and low nonspecific binding. The aim of the present PET study was to examine the radioligand 18 F-AZD4694 in human subjects. Methods: Six control subjects and 10 clinically diagnosed AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
165
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(168 citation statements)
references
References 34 publications
2
165
0
1
Order By: Relevance
“…In general, this white matter uptake has been described to be less pronounced for [ 11 C]PiB as compared to the 18 F labeled compounds, which may somewhat decrease the sensitivity of the 18 Flabeled versions of amyloid tracers. The tracer 18 F-AZD4694 may form an exception, because it has been demonstrated to show comparably lower white matter retention [269]. The apparent differences in tracer distribution between different types of amyloid tracers have raised concerns about the comparability/ standardization of amyloid-PET results.…”
Section: Amyloid-pet Imagingmentioning
confidence: 99%
“…In general, this white matter uptake has been described to be less pronounced for [ 11 C]PiB as compared to the 18 F labeled compounds, which may somewhat decrease the sensitivity of the 18 Flabeled versions of amyloid tracers. The tracer 18 F-AZD4694 may form an exception, because it has been demonstrated to show comparably lower white matter retention [269]. The apparent differences in tracer distribution between different types of amyloid tracers have raised concerns about the comparability/ standardization of amyloid-PET results.…”
Section: Amyloid-pet Imagingmentioning
confidence: 99%
“…20,21 This phase is characterized by a gradual wash-out of radioactivity from both target and reference regions and the time curve for the ratio of radioactivity between target and reference regions is almost stable though with a slight positive slope for several radioligands. [22][23][24][25][26] The SUVR value is viewed as an index for specific binding and its proportionality to the distribution volume ratio (DVR), obtained using fully quantitative PET acquisition and analysis, has been shown for several amyloid radioligands. [22][23][24]26 However, the quasi-steady-state SUVR values are biased in the sense that they overestimate DVR as the time window of acquisition occurs after the peak time of specific binding.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] The SUVR value is viewed as an index for specific binding and its proportionality to the distribution volume ratio (DVR), obtained using fully quantitative PET acquisition and analysis, has been shown for several amyloid radioligands. [22][23][24]26 However, the quasi-steady-state SUVR values are biased in the sense that they overestimate DVR as the time window of acquisition occurs after the peak time of specific binding. 20,27 For amyloid radioligands, the overestimation by quasi-steady-state SUVR has been estimated to be 30% to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Initial in vitro studies demonstrated the high affinity of this compound for Aβ with less binding in the white matter [49]. Further, clinical trials demonstrated the ability of NAV4694 to discriminate between clinically diagnosed patients with AD and normal control subjects with a high degree of test-retest concordance using the reference Logan approach [50]. As a standard for comparison, a study with 25 controls, 10 patients with MCI, 7 with probable AD, and 3 with probable frontotemporal dementia underwent scans with PIB and NAV4694, with similar regions of interests identified on both scans.…”
Section: [ 18 F]-av-1 or [F-18]-bay94-9172 Or Florbetabenmentioning
confidence: 99%